Pedagogical Mediation: Key to Humanizing and Transformative Education. A Look From Aesthetics and Communication - Alzate-Ortiz, Faber Andrés (2020)
This essay proposes an epistemic analysis around pedagogical mediation based on different theoretical and practical elements related to education, communication, and aesthetics, from the horizon of learning intentions in human formation processes. It is assumed that mediation, in itself, is a practice that carries meaning and recognition to people in training and their contexts. Therefore, not only does mediation have properly selected strategies and resources to promote capacity development through the appropriation of plural knowledge, but it also aims to improve those conceptions that have traditionally been about didactics and evaluation. In this order of ideas, throughout the work, it will be possible to recognize, in a singular and propositive way, some positions of conceptual level that suggest thinking of contemporary education from the pedagogical scenario of mediations, facilitating with it that teachers can re-signify all those models, currents and school tendencies that have been based on a transmissive, memorial, and linear formative logic, focused on teaching and little interested in learning.